Main messages for primary care from the 2016 European Guidelines on cardiovascular disease prevention in clinical practice - Piepoli, M; Hoes, A; Brotons, C; Hobbs, R; Corra, U (Taylor and Francis, 2017)
In 2016, a new version of the European Guidelines on Cardiovascular Prevention was released, representing a partnership between the European Association for Cardiovascular Prevention and Rehabilitation of the European Society of Cardiology (ESC) and nine European societies, including Wonca-Europe. The ESC guidelines underscore the importance of a lifetime approach to cardiovascular (CV) risk since both CV risk and prevention are dynamic and continuous as patients' age and/or accumulate co-morbidities. Healthy people of all ages should be encouraged to adopt a healthy lifestyle, as well as improved lifestyle and reduced risk factor levels are paramount in patients at increased risk of developing cardiovascular disease (CVD) and in those with established CVD. Healthcare professionals, and especially general practitioners, play an important role in helping patients achieve this and should set a personal example of healthy lifestyle behaviour. The ESC guidelines are based on 'to do' and 'not to do' messages. Of note, what remains uncertain is stated at the end of each dedicated chapter, confirming that guidelines are not absolute rules, and should be interpreted in the light of the healthcare worker's knowledge and experience, patient preferences and the local social, cultural and economic situation.